PHYTOCHEMICAL ANALYSIS OF THREE ENDANGERED PLANTS (COSTUS SPECIOUS, GLORIOSSA SUPERBA LINN AND RAUVOLFIA SERPENTINE (LINN) BENTH) FROM KANKER DISTRICT OF CHHATTISGARH, INDIA - RAKESH DADSENA, NITISH KUMAR SAHU, SHIRISH AGRWAL, ANIL KUMAR (The Bioscan, 2013)
Chhattisgarh, the herbal state houses with rich and unique biodiversity of medicinal plants which are widely used by traditional healers of the state for treatment of various disease and extensively exploited for commercial purpose which leads to serious threat. Several plants have been studied and listed as rare and endangered which need to be conserved. We selected three such plants viz. Costus specious, Gloriossa superba Linn and Rauvolfia serpentine (Linn) Benth., from Kanker district of Chhattisgarh for their phytochemical analysis by chemical screening and Thin layer chromatography. On primary analysis of the methanolic and ethanolic extract of rhizome of C. specious and G. superba and root and leaves of R. serpentine (Linn) Benth. we found the presence of phytocompounds like saponin, tannins, alkaloids, terpenoids, flavonoids and glycosides in them. This phytocompounds were further separated by TLC using petroleum ether: methanol: benzene (8:1:1.5) as mobile phase in silica gel coated glass plates. Maximum 9 bands were observed in methanolic extract of rhizome of C. specious with Rf value between 0.05 – 0.97 and 6 bands in methanolic extract of rhizome of G. superba with Rf value between 0.02 – 0.94.Similarily in ethanolic and methanolic extract of leaves of R. serpentine (Linn) Benth. Maximum 13 bands were observed with Rf value between 0.05 – 0.96 and 0.04 – 0.98 respectively whereas ethanolic extract of root showed maximum 11 bands with Rf value between 0.04 – 0.98 in comparison with chloroform and petroleum ether extracts. This result can further help in development of new drugs for diseases like cancer and hypertension based on their traditional uses.